2017
DOI: 10.3847/1538-4357/834/2/144
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical Coupling of Mass and Momentum in Multiphase Galactic Winds

Abstract: Using a set of high-resolution hydrodynamical simulations run with the Chollacode, we investigate how mass and momentum couple to the multiphase components of galactic winds. The simulations model the interaction between a hot wind driven by supernova explosions and a cooler, denser cloud of interstellar or circumgalactic media. By resolving scales of Dx 0.1 pc over 100 pc distances, our calculations capture how the cloud disruption leads to a distribution of densities and temperatures in the resulting multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 75 publications
(156 reference statements)
9
146
3
1
Order By: Relevance
“…However, we must caution that the interactions between the winds and the halo gas likely involves processes such as hydrodynamic instabilities and thermal conduction that are unresolved in our our simulations and likely even in galaxy zoom-in simulations with the highest resolution today (e.g. Schneider & Robertson 2017). The evolution of winds inside and outside galactic haloes in galaxy simulations, therefore, likely depends as much on numerics as on the true underlying physics.…”
Section: Wind Recyclingmentioning
confidence: 87%
“…However, we must caution that the interactions between the winds and the halo gas likely involves processes such as hydrodynamic instabilities and thermal conduction that are unresolved in our our simulations and likely even in galaxy zoom-in simulations with the highest resolution today (e.g. Schneider & Robertson 2017). The evolution of winds inside and outside galactic haloes in galaxy simulations, therefore, likely depends as much on numerics as on the true underlying physics.…”
Section: Wind Recyclingmentioning
confidence: 87%
“…Many high-resolution simulations of cold gas clouds in hot flows have shown that entrainment is a highly destructive process, the cold gas being ripped and ionized on time-scales much shorter than needed to reach the observed velocities of hundreds of km s −1 (e.g. Scannapieco & Brüggen 2015;Schneider & Robertson 2017;Sparre et al 2019). In fact, when the density of the cold gas is much higher than the density of the hot gas, the cloud-crushing time t cc , which governs the destruction timescale, is always much lower than the acceleration time t acc because of the drag force, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Veilleux et al 2005). Indeed, it is unclear if any cold, neutral gas is entrained into the wind at all, or if neutral material only re-condenses out of the hot phase at some distance from the host galaxy (e.g., Thompson et al 2016;Krumholz et al 2017;Schneider & Robertson 2017). Thus if CRs are to escape via advection, they must be advecting mainly with the hot, ionised medium, not the cold, neutral one.…”
Section: Diffusion Versus Advective Lossmentioning
confidence: 99%
“…However, the majority of these efforts adopt a purely phenomenological model for CR transport, and attempt to infer quantities such as the diffusive or advective escape time from the spectrum. Similarly, a number of authors have simulated CRs and their role in driving winds from starburst galaxies using a variety of physical models for CR transport (e.g., Booth et al 2013;Hanasz et al 2013;Salem & Bryan 2013;Girichidis et al 2016;Ruszkowski et al 2017). However, in all of these simulations, transport rates and coefficients are left as free parameters that are either set based on empirical estimates from the Milky Way, or are varied in order to perform a parameter study.…”
Section: Introductionmentioning
confidence: 99%